1, 2, 3-Triazolylidene palladium complex with triazole ligand: Synthesis, characterization and application in Suzuki–Miyaura coupling reaction in water. (1st January 2019) - Sasidharan, Drishya; Aji, C.V.; Mathew, Paulson
Graphical abstract: Palladium complex containing 1, 2, 3-triazolylidene and a labile triazole moiety has been prepared and characterized. This mixed palladium complex was found to be highly effective in catalyzing Suzuki–Miyaura coupling reaction between aryl halides and aryl boronic acids in water at room temperature with very low catalyst loading. Abstract: Palladium complex containing 1, 2, 3-triazolylidene and a labile triazole moiety has been prepared and characterized. Simple azide alkyne click reaction using three fold excess of dibromoethane afforded 1-(2-bromoethyl)-4-phenyl-1H-1, 2, 3-triazole. The latter on dehydrobromination yields N-vinyl triazole (Ntzl ) which is subsequently used for preparing its triazolium salt. Further, Ntzl –Pd–Ntzl complex was prepared from triazole by simple palladation which underwent a ligand substitution reaction when treated with in situ generated triazolylidene to form Ctzl –Pd–Ntzl type complex. This mixed palladium complex was found to be highly effective in catalyzing Suzuki–Miyaura coupling reaction between aryl halides and aryl boronic acids in water at room temperature with very low catalyst loading.